Significados que construyen un grupo de miembros activos de la policía nacional con experiencia en escuadrones móviles de carabineros (emcar) frente al posconflicto en Colombia (2018)
This research aims to analyze the meanings that build a group of active members of the National Police with experience in Mobile Squads of Carabineros (EMCAR) against postconflict in Colombia with the Revolutionary Armed Forces of Colombia (FARC). The type of research was descriptive qualitative. The sample consisted of 11 police officers active in the institution with experience in EMCAR; the instrument used for data collection was a semi-structured interview. The analysis allowed to identify the different meanings that the police construct with regard to the knowledge of the conflict and the postconflict in Colombia, evidencing a clear knowledge of the history of the conflict in the country, as well as the affectations that can arise from the postconflict; The meanings of war and peace were built on their work and cultural experiences. Thinking from the peace framework highlights changes at the family level, work and life project.